The Role of Art Exhibitions in Developing Sustainable Tourism in the Kingdom of Saudi Arabia: Diriyah Biennale for Contemporary Art as a Model (Al-Academy, 2025)
Based on the views of the organizers and visitors of Diriyah Biennale of Contemporary Art 2024, this study explored the role of art exhibitions in developing sustainable tourism in the Kingdom of Saudi Arabia and the obstacles deterring this role. The study also investigated the differences in the participants’ views by gender, experience and educational level. The mixed - method combining quantitative and qualitative data analysis was used. Quantitative data was collected via a questionnaire administered to (43) of the organizers. Furthermore, semi-structured interviews were conducted with (67) of the visitors. The results revealed that art exhibitions represented in Diriyah Biennale has an effective role in supporting tourism. The obstacles deterring this role were found to be low. Statistically significant gender differences (a = 0.05) were found in organizers’ views in favor of males regarding the role of art exhibitions in supporting tourism and the obstacles deterring this role. There were also statistically significant differences in the organizers’ views regarding the obstacles in favor of the more experienced (6-10 years). Finally, there are statistically significant differences in the organizers’ view regarding the role of art exhibitions in favor of bachelor degree holders